2013
DOI: 10.1177/0164027512470702
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Exposure to Neighborhood Context

Abstract: Over the last two decades, research has assessed the relationship between neighborhood socioeconomic factors and individual health. However, existing research is based almost exclusively on cross-sectional data, ignoring the complexity in health transitions that may be shaped by long term residential exposures. We address these limitations by specifying distinct health transitions over multiple waves of a 15 year study of American adults. We focus on transitions between a hierarchy of health states, (free from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 73 publications
6
58
0
Order By: Relevance
“…Consistent with our predictions, the association between neighborhood disadvantage and physical aggression was stronger with longer study periods. This may have been caused by cumulative exposure to disadvantaged neighborhoods, which increased the adverse effects of disadvantage (Clarke et al, 2014). In a longitudinal study, Wodtke et al (2011) followed 4,154 participants aged 1-17 years, and found that sustained exposure to disadvantaged neighborhoods had a more profound impact than the effects apparent in studies with short follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our predictions, the association between neighborhood disadvantage and physical aggression was stronger with longer study periods. This may have been caused by cumulative exposure to disadvantaged neighborhoods, which increased the adverse effects of disadvantage (Clarke et al, 2014). In a longitudinal study, Wodtke et al (2011) followed 4,154 participants aged 1-17 years, and found that sustained exposure to disadvantaged neighborhoods had a more profound impact than the effects apparent in studies with short follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented significant associations between objective or subjective neighborhood factors and individual health outcomes, net of personal characteristics (see Balfour and Kaplan 2002;Clarke et al 2014;Diez Roux 2001;Do et al 2008;Ellaway, Macintyre, and Kearns 2001;Kawachi and Berkman 2003;Siordia and Saenz 2013;Wen, Hawkley, and Cacioppo 2006;Weden, Carpiano, and Robert 2008;Yen et al 2008). For example, the availability of recreational parks and bus routes has been found to be positively associated with levels of physical activity participation, thus indirectly promoting health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The primary contextual factors examined in many multilevel studies are those associated with economic advantage and disadvantage (see e.g., Brooks-Gunn, Duncan, and Aber 1997; Clarke et al 2014). The role of local socioeconomic status (SES) in shaping the health of all residents is an important connection to address – it is consistently influential across outcomes, and may shape health through a myriad of pathways.…”
Section: The Role Of Context In Maternal Smoking: Space For Advancementmentioning
confidence: 99%